MENENTUKAN ARAHAN FUNGSI LAHAN DAERAH ALIRAN SUNGAI NOELMINA DENGAN APLIKASI SISTEM INFORMASI GEOGRAFIS (SIG) - Kumalajati, Erlynda (Universitas Tadulako, 2017)
Data processing using Geographic Information System (GIS) can provide some spatial and attributes information, including information for determining the area function direction. Area function direction of Noelmina watershed in East Nusa Tenggara was determined based on the function determination criterias, Keputusan Presiden Nomor 32 Tahun 1990 on protective area management and SK Menteri Pertanian Nomor 837/KPTS/ Um/11/1980 and 683/KPTS/Um/8/1981 on the criteria and procedures of protected and production forests establishment. The study objectives is to classify Noelmina watershed area using GIS application and the latest rainfall data. Â The classification of Noelmina watershed area indicates that Noelmina watershed is classified into 4 area functional directions, ie the protected zone area of 58,395.22 ha, the buffer zone area of 94,094.26 ha, the annual cultivation area of 19,517.48 ha, and the crop cultivation area of 25,144.46 ha. The dominant function area is the buffer zone area of 47,73% from watershed area.